Peran Instagram dalam Promosi Program Ruang Pulih oleh Bicara Project - Nadia Aliya; Abung Supama Wijaya; Renny Soelistiyowati (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
This study examines the role of Instagram in promoting the Ruang Pulih program by Bicara Project. The research problem arises from the limited studies integrating the approaches of Integrated Marketing Communication (IMC), emotional branding, and Uses and Gratifications (U&G) in the promotion of psychology-based programs. This study aims to analyze Instagram promotional strategies in building audience awareness and engagement, as well as to identify the forms of audience engagement generated through the promotional content of the Ruang Pulih program. The research employed a descriptive qualitative approach, with data collected through observation, interviews, active participation, and literature review. Primary data were obtained through the researcher’s involvement in promotional activities at Bicara Project and interviews with informants, while secondary data were gathered from relevant references. The collected data were analyzed using descriptive qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. Data validity was enhanced through source triangulation. The results indicate that promotional activities were carried out systematically through reels and carousel formats distributed consistently on Instagram. Emotional and relatable reels content was found to generate higher audience engagement than informative carousel content, both in terms of interaction quantity and response quality. Audiences tended to provide more personal and reflective comments, demonstrating emotional connections to the issues presented in the content. These findings suggest that promotional success is influenced by emotional approaches, content formats, and the alignment of messages with audience needs and experiences.